Few European adults are living a healthy lifestyle - Marques, A. (2019)
Purpose:This study aimed to measure healthy lifestyle for European adults. Design:Cross-sectional study. Settings:In 20 European countries. Participants:A total of 34 993 (16 749 men, 18 244 women) European adults. Measures:Data were from the 2014 European Social Survey (n ¼ 34 993) on 4 modifiable behaviors (physical activity, fruit and vegetable consumption, not drinking alcohol to excess, and not smoking) as well as sleep quality. Analysis:Behaviors were combined and formed a healthy lifestyle measure. Binary logistic regression was done to determine associations of healthy lifestyle and sociodemographic characteristics. Results:Only 5.8% of the adults reported a healthy lifestyle. The prevalence of having a healthy lifestyle varied among European countries. The lowest rates were in Hungary (1.3%) and Czech Republic (1.9%). The highest rates were in United Kingdom (8.6%) and Finland (9.2%). Those who presented a higher likelihood of having a healthy lifestyle were middle age (odds ratio [OR] ¼ 1.20), older people (OR ¼ 1.34), having higher household income (OR ¼ 1.33), being a student (OR ¼ 1.38), and retired (OR ¼ 1.31). Those less likely to have a healthy lifestyle were lived without a partner (OR ¼ 0.82), unemployed (OR ¼ 0.73), and lived in rural areas (OR ¼ 0.86). Conclusions:Few European adults were practicing 5 healthy behaviors. This should be a message for governments and be considered in the establishment of preventive public policies in the areas of health and health education.